Integrative and complementary practices in health residences of the university hospital (Research, Society and Development, 2022)
Objective: to evaluate the applicability of Integrative and Complementary Practices among second-year residents of a university hospital in Alagoas. Method: this is an exploratory-descriptive study with a qualitative approach carried out in the year 2021, in a university hospital, using the interview as a data collection technique. The data were submitted to content analysis according to the Malheiros methodology. Results: the categories found were - knowledge in relation to Integrative and Complementary Practices and experiences with Integrative and Complementary Practices. From the analysis, it became noticeable the lack of knowledge of some residents on the subject; the participants reflect on the need for better and greater knowledge about Integrative and Complementary Practices. It is clear the need to acquire experience and knowledge of Integrative and Complementary Practices in health education and the importance of this topic for the multidisciplinary team. Conclusion: the study contributed in the scope of professional practice, through dialogue about it, aiming to stimulate the search for more knowledge and the implementation of Integrative and Complementary Practices in residency teaching in health and, therefore, in the assistance to the user of health services.